Cuarta Bienal de la Habana 1991. - Bienal La Habana 1991 (La Habana : Centro Wifredo Lam, 1991)
Acosta, Gustavo ; Adrus, Said ; Aguilera Gonzalez, Alejandra ; Akuda, Fanizani ; Al Wechahi, Abdel Hady ; Altamirano, Carlos ; Amaral, Zulmira ; Ambar, Iene ; Andrade, José Zan ; Andre, Marcus ; etc.
Cuarta Bienal de la Habana 1991, La Habana, 1991
boek